THE RELATIONSHIP BETWEEN POVERTY AND GROWTH IN NIGERIA - Alumona, Steven; Onyernama, Jude Chidi; Egwu, Chijioke (CENTRAL ASIA AND THE CAUCASUS, 2024)
This study focused on the relationship between poverty and growth in Nigeria. The research method adopted was a multiple linear regression model. The ordinary least square (OLS) technique and e-views software were used for the data analysis. The dependent variable used for the purpose of the research was the gross domestic product. While the independent variables were population growth rate, exchange rate, unemployment rate, investment and inflation rate. Data were collected from the Central bank Statistical Bulletin, National Bureau of Statistics and the World development indicators, covering the years 1981-2013. The result obtained shows that economic growth in the short run has a positive relationship with poverty, but in the long they have a negative relationship. Furthermore, the study showed that there is a significant relationship between economic growth and poverty, but there is no causation. It was recommended that government projects should focus on human capital development as they empower a greater fraction of the populace to contribute meaningfully to the economy. Finally, inequality in income distribution should be checked as it is driving force to poverty